2010
DOI: 10.1371/journal.pone.0014326
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Toll-Like Receptors Are Not Associated with Rheumatoid Arthritis Susceptibility or Anti-Tumour Necrosis Factor Treatment Outcome

Abstract: BackgroundSeveral studies point to a role of Toll-like receptors (TLRs) in the development of rheumatoid arthritis (RA). We investigated if genetic variants in TLR genes are associated with RA and response to tumour necrosis factor blocking (anti-TNF) medication.Methodology and Principal Findings22 single nucleotide polymorphisms (SNPs) in seven TLR genes were genotyped in a Dutch cohort consisting of 378 RA patients and 294 controls. Significantly associated variants were investigated in replication cohorts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…While monitoring can help to identify non-responders early and allow switching to another treatment, the causes of non-response or loss of response remain, in most cases, elusive. Although it is possible that the clinical manifestations of RA may be driven by different pathways in different subjects, the multifactorial nature of the disease has made identification of robust biomarkers challenging, thus highlighting a significant unmet need 3335. In this small phase I study, mavrilimumab demonstrated an adequate safety profile when administered as a single, escalating intravenous dose of 0.01–10.0 mg/kg in subjects with RA.…”
Section: Discussionmentioning
confidence: 90%
“…While monitoring can help to identify non-responders early and allow switching to another treatment, the causes of non-response or loss of response remain, in most cases, elusive. Although it is possible that the clinical manifestations of RA may be driven by different pathways in different subjects, the multifactorial nature of the disease has made identification of robust biomarkers challenging, thus highlighting a significant unmet need 3335. In this small phase I study, mavrilimumab demonstrated an adequate safety profile when administered as a single, escalating intravenous dose of 0.01–10.0 mg/kg in subjects with RA.…”
Section: Discussionmentioning
confidence: 90%
“…The results somewhat vary from region to region. The TLR9 SNP rs187084 allele variant TT may increase RA susceptibility in the Turkish RA population, although it was not associated in studies of Dutch or French cohorts [100][101][102]. Furthermore, the SNP rs5741883 of TLR8 has been reavealed to have association with rheumatoid factor autoantibody positivity in a cohort study on 319 European individuals [103].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Ahmad-Nejad et al, 2004;Alvarez-Rodriguez et al, 2011;Brand et al, 2005;Britton et al, 2001;Coenen et al, 2010;Feldmann et al, 2002;Gazouli et al, 2005;Hoffman et al, 2001Hoffman et al, , 2003Neven et al, 2004;Pontillo et al, 2011;Schoultz et al, 2009;Shen et al, 2010;Snelgrove et al, 2007;Villani et al, 2009;Yang et al, 2011)…”
unclassified